EFFICIENCY OF DIVERSIFIED RICE-WHEAT CROPPING SYSTEMS INCLUDING POTATO, VEGETABLE PEAS AND GROUNDNUT CROPS IN TRANS-GANGETIC PLAINS - Singh, J. P; Salaria, A; Singh, K; Gangwar, B. (Potato Journal, 2013)
Field experiment was conducted during 2000-2003 on diversified rice-wheat cropping systems involving potato, vegetable peas and groundnut, and water management treatments in rice to increase the production, economics and water use >efficiency. Inclusion of potato, vegetable peas and groundnut in rice-wheat cropping system increased the production, economics and land use efficiency on an average by 95, 75 and 11 percent, respectively. Rice equivalent yield (REY) was maximum in rice/ groundnut/rice(R/G/R)-potato-wheat (24.60 t/ha/yr), which was at par with rice-potato-wheat (24.27 t/ha/yr) followed by ricevegetable peas-wheat (19.02 t/ha/yr) as against traditional rice-wheat (11.63 t/ha/yr) system. Net returns was the highest in ricevegetable peas-wheat (Rs.67540/ha/yr) system, which was at par with R/G/R-potato-wheat (Rs.67424/ha/yr) and rice-potato-wheat (Rs.64906/ha/yr) as against rice-wheat (Rs.38159/ha/yr) system. Irrigation to rice crop at hairline cracks (HC) in soil saved about 20 percent of total water use on an average in different cropping systems compared to traditional system of irrigating rice at disappearance of ponded water (DP). Decline in available soil K ranging from 4.0 to 12.0 percent and build up of available soil P from 41.7 to 62.5 percent was recorded from initial soil test values after 3 years in different cropping systems. The apparent soil nutrient balance (gain/loss) was negative for K (243-440 kg/ha) and positive for P (57.6-151.1 kg/ha) with varying degrees in different cropping systems.